WEALTH AND CHILDREN AS FITNAH IN THE QUR’AN: A COMPARATIVE STUDY OF TAFSIR AL-AZHAR BY HAMKA AND TAFSĪR AL-MUNĪR BY WAHBAH AL-ZUHAYLĪ - Zulkarnain, Ahmad; Khasanah, Rofiatul (Sekolah Tinggi Agama Islam Sadra, 2024)
This research will discuss fitnah concerning wealth and children in Q.S. Al-Anfāl [8]: 28 and Q.S. Taghābun [64]: 15 to know whether the bestowal of wealth and children makes humans able to be grateful or instead makes them negligent of the commands of Allah Swt. The author chooses Al-Azhar and al-Munīr as the sources of research related to wealth and children as fitnah. This research is qualitative using library research with a comparative approach. The primary data sources used are the Qur’an and the commentaries Al-Azhar and al-Munīr. The secondary data sources are the opinions of scholars, books of interpretation, journals, and books related to the research theme. The results of this study indicate that there are differences and similarities in the interpretation of property and children as fitnah. It is influenced by differences in interpretation methods, styles, and sources used by both music which directly affect the meaning of interpretation. Hamka in his Tafsir Al-Azhar explains that the existence of wealth and children makes humans proud and happy, which makes humans forget Allah and makes humans afraid of death, cowardly, afraid to fight unwilling to sacrifice, and reluctant to help others. Meanwhile, Wahbah al-Zuḥaylī explains that wealth and children are fitnah, namely sin and punishment because they can occupy the heart with the world and prevent it from helping others.